Blocking oestradiol synthesis pathways with potent and selective coumarin derivatives - Sanna Niinivehmas; Pekka A. Postila; Sanna Rauhamäki; Elangovan Manivannan; Sami Kortet; Mira Ahinko; Pasi Huuskonen; Niina Nyberg; Pasi Koskimies; Sakari Lätti; Elina Multamäki; Risto O. Juvonen; et al. (Taylor & Francis Group, 2018)
A comprehensive set of 3-phenylcoumarin analogues with polar substituents was synthesised for blocking oestradiol synthesis by 17-β-hydroxysteroid dehydrogenase 1 (HSD1) in the latter part of the sulphatase pathway. Five analogues produced ≥62% HSD1 inhibition at 5 µM and, furthermore, three of them produced ≥68% inhibition at 1 µM. A docking-based structure-activity relationship analysis was done to determine the molecular basis of the inhibition and the cross-reactivity of the analogues was tested against oestrogen receptor, aromatase, cytochrome P450 1A2, and monoamine oxidases. Most of the analogues are only modestly active with 17-β-hydroxysteroid dehydrogenase 2 - a requirement for lowering effective oestradiol levels in vivo. Moreover, the analysis led to the synthesis and discovery of 3-imidazolecoumarin as a potent aromatase inhibitor. In short, coumarin core can be tailored with specific ring and polar moiety substitutions to block either the sulphatase pathway or the aromatase pathway for treating breast cancer and endometriosis.